Clozapine‐induced myocarditis: Follow‐up for 3.5 years after successful retrial. (27th February 2019) - Otsuka, Yuji; Idemoto, Keita; Hosoda, Yutaka; Imamura, Yukitsugu; Aoki, Tsutomu
Abstract: Schizophrenia patients have significantly lower life expectancy than the general population. Clozapine is the most effective antipsychotic to reduce the mortality rate in these patients. Here, we report a schizophrenic patient with clozapine‐induced myocarditis and successful retrial. In the first trial, clozapine was discontinued due to myocarditis. In the second trial, the titration rate was slower, and sodium valproate was not coadministered with clozapine. The patient has not developed myocarditis over 3.5 years of observation. It may be possible to take clozapine for a long time even after clozapine‐induced myocarditis, and thus improve the life expectancy of schizophrenia patients. Abstract : We reported a case of clozapine‐induced myocarditis with successful reintroduction of clozapine. Rechallenge succeeded due to slower titration and cessation of sodium valproate. Clozapine may be taken for a long time even after clozapine‐induced myocarditis to improve life expectancy in schizophrenia patients.